2008
DOI: 10.1074/jbc.m706861200
|View full text |Cite
|
Sign up to set email alerts
|

Unique Properties of Plasmodium falciparum Porphobilinogen Deaminase

Abstract: The hybrid pathway for heme biosynthesis in the malarial parasite proposes the involvement of parasite genome-coded enzymes of the pathway localized in different compartments such as apicoplast, mitochondria, and cytosol. However, knowledge on the functionality and localization of many of these enzymes is not available. In this study, we demonstrate that porphobilinogen deaminase encoded by the Plasmodium falciparum genome (PfPBGD) has several unique biochemical properties. Studies carried out with PfPBGD part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 39 publications
4
35
2
Order By: Relevance
“…An apicoplast pathway to synthesise isopentenyl diphosphate (IPP) – a precursor of isoprenoids for prenylation of proteins, ubiquinone side chains, dolichols and modification of tRNAs (Ralph et al, 2004) – was also identified from the genome data (Jomaa et al, 1999; Guggisberg et al, 2014a; Imlay and Odom, 2014; Armstrong et al, 2015; Imlay et al, 2015). Subsequent data mining revealed that the apicoplast of malaria parasites makes iron sulphur complexes (Seeber, 2002, 2003; Ralph et al, 2004) and cooperates with the mitochondrion in the synthesis of haem (Ralph et al, 2004; Sato et al, 2004; van Dooren et al, 2006; Nagaraj et al, 2008, 2009a,b; Shanmugam et al, 2010). These four anabolic roles for the apicoplast hinted that synthesis of crucial precursors was the essential role of the apicoplast, but the genes did not tell us exactly what was made and how it was essential.…”
Section: Function Of the Apicoplastmentioning
confidence: 99%
“…An apicoplast pathway to synthesise isopentenyl diphosphate (IPP) – a precursor of isoprenoids for prenylation of proteins, ubiquinone side chains, dolichols and modification of tRNAs (Ralph et al, 2004) – was also identified from the genome data (Jomaa et al, 1999; Guggisberg et al, 2014a; Imlay and Odom, 2014; Armstrong et al, 2015; Imlay et al, 2015). Subsequent data mining revealed that the apicoplast of malaria parasites makes iron sulphur complexes (Seeber, 2002, 2003; Ralph et al, 2004) and cooperates with the mitochondrion in the synthesis of haem (Ralph et al, 2004; Sato et al, 2004; van Dooren et al, 2006; Nagaraj et al, 2008, 2009a,b; Shanmugam et al, 2010). These four anabolic roles for the apicoplast hinted that synthesis of crucial precursors was the essential role of the apicoplast, but the genes did not tell us exactly what was made and how it was essential.…”
Section: Function Of the Apicoplastmentioning
confidence: 99%
“…Iron is an essential cofactor for the DNA replication enzyme ribonucleotide reductase, and as a result iron is required to fuel this rapid intra-erythrocytic proliferation (Rubin et al, 1993). Iron is also utilized by the parasite for pyrimidine (Krungkrai et al, 1990; Van Dooren et al, 2006) and heme biosynthesis (Sato and Wilson, 2002; Dhanasekaran et al, 2004; Sato et al, 2004; Nagaraj et al, 2008, 2009, 2010, 2013). As with the human host, the malaria parasite must also balance its need for iron against the cytotoxicity of iron.…”
Section: Iron Metabolism In the Malaria Parasitementioning
confidence: 99%
“…The first enzyme, δ-aminolevulinate synthase ( Pf ALAS) [8], [9], and the last two enzymes, Protoporphyrinogen IX oxidase ( Pf PPO) and Ferrochelatase ( Pf FC) [10], [11] localize to the mitochondrion. The enzymes that catalyze the intermediate steps: ALA dehydratase ( Pf ALAD) [12], [13], Porphobilinogen deaminase ( Pf PBGD) [9], [14], and Uroporphyrinogen III decarboxylase ( Pf UROD) [15] localize to the apicoplast (a chloroplast relic), whereas, the next enzyme Coproporphyrinogen III oxidase ( Pf CPO) is cytosolic [16]. Figure 1 depicts the pathway.…”
Section: Introductionmentioning
confidence: 99%